2021
DOI: 10.1007/s00604-021-04918-7
|View full text |Cite
|
Sign up to set email alerts
|

Monose-modified organic electrochemical transistors for cell surface glycan analysis via competitive recognition to enzyme-labeled lectin

Abstract: A competitive strategy for glycan determination on cell surface with organic electrochemical transistors (OECTs) has been developed. The carboxylic multi-wall carbon nanotubes were firstly immobilized on the gate interface to cross-link the specific monose with adipic dihydrazide as the linker, which could then competitively recognize horseradish peroxidase (HRP)-labeled lectin with the target monose on the cell surface. The HRP captured on the gate interface through the affinity of lectin to monose finally ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(38 reference statements)
2
6
0
Order By: Relevance
“…Three miRNAs were observed to be upregulated in PCa cell lines and tissues in a recent study, and consistent overexpression of these miRNAs was found in several types of clinical samples, including plasma and urine from PCa patients 20,21,55 . Furthermore, these miRNAs have been implicated in the presence of cancer and have been shown to promote various cancer progression, migration, or invasion 56–59 . Our results confirmed that miR‐148a‐3p (mean RQ = 19.45 ± 34.51; p < 0.01), miR‐483‐5p (mean RQ = 49.53 ± 60.83; p < 0.001), and miR‐574‐3p (mean RQ = 17.28 ± 18.82; p < 0.001) were overexpressed in PCa compared to the control samples (mean RQ = 2.27 ± 2.73, 1.44 ± 1.58, and 1.35 ± 1.29, respectively).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Three miRNAs were observed to be upregulated in PCa cell lines and tissues in a recent study, and consistent overexpression of these miRNAs was found in several types of clinical samples, including plasma and urine from PCa patients 20,21,55 . Furthermore, these miRNAs have been implicated in the presence of cancer and have been shown to promote various cancer progression, migration, or invasion 56–59 . Our results confirmed that miR‐148a‐3p (mean RQ = 19.45 ± 34.51; p < 0.01), miR‐483‐5p (mean RQ = 49.53 ± 60.83; p < 0.001), and miR‐574‐3p (mean RQ = 17.28 ± 18.82; p < 0.001) were overexpressed in PCa compared to the control samples (mean RQ = 2.27 ± 2.73, 1.44 ± 1.58, and 1.35 ± 1.29, respectively).…”
Section: Resultssupporting
confidence: 87%
“…20,21,55 Furthermore, these miRNAs have been implicated in the presence of cancer and have been shown to promote various cancer progression, migration, or invasion. [56][57][58][59] Our results confirmed…”
Section: Circulating Mirnas In Clinical Specimens Using Hazis-cirrsupporting
confidence: 85%
See 2 more Smart Citations
“…[ 14 , 15 , 16 , 17 , 18 , 19 , 20 ] Electrochemical transistors have been considered to fulfill the portable device requirements of high‐throughput, ultrasensitive, cost‐effective, rapidly, and real‐time detection without amplification, and any chemical or biological labeling. [ 21 ] Diverse kinds of sensors, including DNA, [ 22 , 23 ] protein, [ 24 , 25 ] cell, [ 26 ] neurotransmitter, [ 27 , 28 , 29 ] virus, [ 30 , 31 ] glucose, [ 32 , 33 ] glycans, [ 34 , 35 ] ion, [ 36 , 37 , 38 ] and growth factor sensors [ 39 ] are designed based on transistors. SGGTs have been utilized in diverse biosensors due to their excellent biocompatibility, chemical stability, high mobility, and the ability to work at less than 1 V. SGGTs have been used in the detection of let‐7b, [ 40 , 41 ] miRNA‐4484, [ 42 ] and other common kinds of miRNA.…”
Section: Introductionmentioning
confidence: 99%